2015
DOI: 10.4314/ijbcs.v9i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Fascioliasis in cattle slaughtered at Gombe abattoir, Nigeria

Abstract: A study to determine the prevalence of fascioliasis in cattle slaughtered at the Gombe township abattoir was carried out from April -June 2009. Three hundred and twenty livers and bile ducts of four breeds of cattle slaughtered at the abattoir were examined for fascioliasis at postmortem. The four breeds of cattle were White Fulani (155), Red Bororo (92), Sokoto Gudali (53) and Muturu (20). An overall prevalence of 83 (25.9%) was recorded. The white Fulani breed was the most infected, with a prevalence of 56 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
4
2
Order By: Relevance
“…According to Ibrahim et al, [32], there is a hormone-controlled relaxation of immunity in female animals during pregnancy and breastfeeding, which increases vulnerability to infection. However, this finding conflicts with the findings of Adang et al, (2015) [25] in Nigeria and Eze and Brigg (2018) [33] in Nigeria, who found greater prevalence in males than females.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…According to Ibrahim et al, [32], there is a hormone-controlled relaxation of immunity in female animals during pregnancy and breastfeeding, which increases vulnerability to infection. However, this finding conflicts with the findings of Adang et al, (2015) [25] in Nigeria and Eze and Brigg (2018) [33] in Nigeria, who found greater prevalence in males than females.…”
Section: Discussioncontrasting
confidence: 80%
“…This is lower than the 48.0% reported by Ieren et al, (2016) [13] in Zaria, the 32.34% obtained by Yatswako and Alhaji (2017) [19] in North-central Nigeria after a ten-year retrospective study, the 64.4% reported by Nyirenda (2019) [15] in Mongu area of Zambia, the 46.54% by Hassan and Anwo (2010) [20] in Isheri-Olofin, the 54. 0% by Idris et al, (2004) [21] in Gwagwalada abattoir, and the 60.74% by Wulha and Banke (2001) [22] in Markurdi metropolis. However, this observation is higher than the 18.0% reported by Abolarin and Aroyehun (2005) [23] in the Minna abattoir, 27.68% by Magaji (2014) [24] in the Sokoto Metropolitan Abattoir, and 25.9% reported by Adang et al, (2015) [25].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These areas attract both local and migratory species of birds and thus are ideal locations for avifaunal surveys (Grimmett & Inskipp, 2007;Fischer & Islam, 2020;Guthula et al, 2022). Bird population, abundance and diversity are important indicators to know the biological richness and overall health of an ecosystem (Adang et al, 2015;Dendup et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic environments, freshwater snails are good bioindicators of chemical pollution because they can accumulate and concentrate in their bodies large amounts of toxic heavy metals (Bouthir et al, 2004). Otherwise, freshwater snails play the role of obligate intermediate hosts for infectious agents, among which the most frequently cited are cercariae of the digenetic trematodes worms (flukes) belonging to the genus Fasciala and Schistosoma, responsible for human and cattle chronic infection fascioliasis and schistosomiasis respectively (Ntonifor and Ajayi, 2007;Dawet et al, 2012;Adang et al, 2015). Among the snails mentioned there are freshwater species of the genera Biomphalaria, Bulinus, Oncomelania and Planorbarius whose presence in water points (streams, river edges and swamps) is a major risk factor for the spread of bilharzia (Dreyfuss and Rondelaud, 2011;Bridger et al, 2018;Chibwana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%